A new species of the genus Trichromothrips (Thysanoptera, Thripidae) from bamboo in Thailand, Malaysia and Vietnam - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2011)
Trichromothrips dorsalis sp. n. is described from bamboo in Thailand, Malaysia and Vietnam. This new species is similar to T. alis Bhatti from India, but is distinguished by having large median dark areas on abdominal tergites III–VII. This is the first record of this genus from Thailand and Vietnam.